 Mathematics
15 May, 09:00

# A teacher used the change of base formula to determine whether the equation below is correct.(log Subscript 2 Baseline 10) (log Subscript 4 Baseline 8) (log Subscript 10 Baseline 4) = 3Which statement explains whether the equation is correct?

+2
1. 15 May, 10:39
0
The equation is correct

Step-by-step explanation:

The equation, written as:

[log_2 (10) ][log_4 (8) ][log_10 (4) ] = 3

Consider the change of base formula:

log_a (x) = [log_10 (x) ] / [log_10 (a) ]

Applying the change of base formula to change the expressions in base 2 and base 4 to base 10.

(1)

log_2 (10) = [log_10 (10) ]/[log_10 (2) ]

= 1/[log_10 (2) ]

(Because log_10 (10) = 1)

(2)

log_4 (8) = [log_10 (8) ]/[log_10 (4) ]

Now putting the values of these new logs in base 10 into the left-hand side of original equation to verify if we have 3, we have:

[log_10 (2) ][log_8 (4) ][log_10 (4) ]

= [1 / log_10 (2) ][log_10 (8) / log_10 (4) ][log_10 (4) ]

= [1/log_10 (2) ] [log_10 (8) ]

= [log_10 (8) ]/[log_10 (2) ]

= [log_10 (2³) ]/[log_10 (2) ]

Since log_b (a^x) = xlog_b (a)

= 3[log_10 (2) ]/[log_10 (2) ]

= 3 as required

Therefore, the left hand side of the equation is equal to the right hand side of the equation.